Pengukuran Kinerja Teknologi Informasi di Indonesia dalam General Control: Literature Review - Puguh Jayadi; Puji Sarwono; Melgisaputra Dwi Nanda (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2022)
Performance measurement as an agency's internal audit process in the context of Information Technology General Control (ITGC) functions to track, study and provide results on how to apply Information Technology (IT) in an agency. The implementation of the internal audit framework used helps provide better IT recommendations. With the Semantic Lirature Review (SLR) on several research results on the application of IT performance measurement in Indonesia, it aims to find out what agencies are implementing, the framework used and how the results of the implementation of performance measurement are. From the results of the search with the SLR, it provides several conclusions including a description of the condition of IT and recommendations for better IT implementation, and it is possible to continue to develop or integrate parts of the performance measurement framework to provide better IT audit results and increase the variety of contributions in the audit field. IT in particular in an effort to ensure the continuity of IT as needed.Keywords— Information Technology, General Control, Semantic Literature Review, Framework, Internal Audit